Sprouty-Related Ena/Vasodilator-Stimulated Phosphoprotein Homology 1-Domain–Containing Protein-2 Critically Regulates Influenza A Virus–Induced Pneumonia. Issue 7 (July 2016) - Ito, Toshihiro; Itakura, Junya; Takahashi, Sakuma; Sato, Miwa; Mino, Megumi; Fushimi, Soichiro; Yamada, Masao; Morishima, Tuneo; Kunkel, Steven L.; Matsukawa, Akihiro
Abstract : Objectives: Influenza A virus causes acute respiratory infections that induce annual epidemics and occasional pandemics. Although a number of studies indicated that the virus-induced intracellular signaling events are important in combating influenza virus infection, the mechanism how specific molecule plays a critical role among various intracellular signaling events remains unknown. Raf/MEK/extracellular signal-regulated kinase cascade is one of the key signaling pathways during influenza virus infection, and the Sprouty-related Ena/vasodilator-stimulated phosphoprotein homology 1-domain–containing protein has recently been identified as a negative regulator of Raf-dependent extracellular signal-regulated kinase activation. Here, we examined the role of Raf/MEK/extracellular signal-regulated kinase cascade through sprouty-related Ena/vasodilator-stimulated phosphoprotein homology 1-domain–containing protein in influenza A viral infection because the expression of sprouty-related Ena/vasodilator-stimulated phosphoprotein homology 1-domain–containing protein was significantly enhanced in human influenza viral–induced pneumonia autopsy samples. Design: Prospective animal trial. Setting: Research laboratory. Subjects: Wild-type and sprouty-related Ena/vasodilator-stimulated phosphoprotein homology 1-domain–containing protein-2 knockout mice inoculated with influenza A. Interventions: Wild-type or sprouty-related Ena/vasodilator-stimulated phosphoprotein homology 1-domain–containing protein-2 knockout mice were infected by intranasal inoculation of influenza A (A/PR/8). An equal volume of phosphate-buffered saline was inoculated intranasally into mock-infected mice. Measurements and Main Results: Influenza A infection of sprouty-related Ena/vasodilator-stimulated phosphoprotein homology 1-domain–containing protein-2 knockout mice led to higher mortality with greater viral load, excessive inflammation, and enhanced cytokine production than wild-type mice. Administration of MEK inhibitor, U0126, improved mortality and reduced both viral load and cytokine levels. Furthermore, bone marrow chimeras indicated that influenza A–induced lung pathology was most severe when sprouty-related Ena/vasodilator-stimulated phosphoprotein homology 1-domain–containing protein-2 expression was lacking in nonimmune cell populations. Furthermore, microarray analysis revealed knockdown of sprouty-related Ena/vasodilator-stimulated phosphoprotein homology 1-domain–containing protein-2 led to enhanced phosphatidylinositol 3-kinase signaling pathway, resulting that viral clearance was regulated by sprouty-related Ena/vasodilator-stimulated phosphoprotein homology 1-domain–containing protein-2 expression through the phosphatidylinositol 3-kinase signaling pathway in murine lung epithelial cells. Conclusions: These data support an important function of sprouty-related Ena/vasodilator-stimulated phosphoprotein homology 1-domain–containing protein-2 in controlling influenza virus–induced pneumonia and viral replication. Sprouty-related Ena/vasodilator-stimulated phosphoprotein homology 1-domain–containing protein-2 may be a novel therapeutic target for controlling the immune response against influenza influenza A virus infection. Abstract : Supplemental Digital Content is available in the text.